Analyzing the Relationship Between Environmental Variables, Job Demands, Emotional Fatigue, and Job Stress in the Metal Industry of Southern Peninsular Malaysia - Mohd Azrin, Mohd Said; Nor Kamaliana, Khamis; Khairul’Aqil, Khairulnisan; Mohd Anas, Mohd Sabri; Ahmad Rasdan, Ismail (Penerbit UTM Press, 2025)
Occupational environmental stress significantly impacts employees' efficiency, wellbeing, and safety within the workplace. This study aimed to evaluate such stress in the metal workplace by scrutinizing environmental factors: temperature, relative humidity, noise, and illuminance. This study employed mixed data collection methods, combining both objective and subjective approaches. Four (4) metal workplaces were conveniently selected, and questionnaires with 159 subjective evaluation items were distributed to 60 respondents. The methods involved collecting empirical data on environmental factors. Pearson correlation and regression analysis revealed a strong correlation between occupational environmental factors and both objective physical assessments and subjective evaluations. Temperature data exhibited the highest association, followed by relative humidity, noise, and illuminance. Further, a multivariate regression analysis highlighted a robust positive correlation (r=0.834) and a regression value (R2=0.785) between environmental variables and the job stress level. This study highlights the relationship between job stress levels and their impact on workers in the workplace. It also introduces a new model for predicting occupational environmental stress at work. In conclusion, this research provides valuable insights for stakeholders by ensuring workplaces align with standards that promote employees' well-being, safety, and physical and psychological health. Such findings facilitate the creation of conducive work environments.